2013
DOI: 10.3126/ije.v2i1.9226
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical And Antibacterial Activityof Leave Extracts Of Guiera Senegalensis Lam On Selected Species Of Gram Positive And Gram Negative Bacteria

Abstract: The aim of this study was to determine the preliminary phytochemical component and antibacterial activity of the leaves extract of Guiera senegalensis lam (Combretaceae) against three clinical isolates (Staphylococcus aureus, E. coli and Klebsiella species) using standard method of analysis. The test for phytochemical component revealed the presence of alkaloid, anthraquinolones, tannin and phlobatanins. The result of antibacterial activity showed that the ethanolic extract exhibit higher zone of inhibition ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(17 reference statements)
0
4
0
2
Order By: Relevance
“…Although many plants were reported to cure nausea, vomiting and diarrhea, G. senegalensis had a FL of 100% for these ailments, indicating consensus among all of the respondents who cited G. senegalensis; thus, this plant appeared to be the most important plant species identified in this study. Many studies (Yagana et al, 2012;Djifaby et al, 2012;Mamman and Isa, 2013; Sombié et al, 2013) support the use of G. senegalensis for antimicrobial activities. Kim and Lean (2013), however, reported that Anastatica hierochuntica L. is the most common herb used by pregnant women in Malaysia.…”
Section: Relative Frequency Of Citation (Rfc) and Fidelity Level (Fl)mentioning
confidence: 92%
“…Although many plants were reported to cure nausea, vomiting and diarrhea, G. senegalensis had a FL of 100% for these ailments, indicating consensus among all of the respondents who cited G. senegalensis; thus, this plant appeared to be the most important plant species identified in this study. Many studies (Yagana et al, 2012;Djifaby et al, 2012;Mamman and Isa, 2013; Sombié et al, 2013) support the use of G. senegalensis for antimicrobial activities. Kim and Lean (2013), however, reported that Anastatica hierochuntica L. is the most common herb used by pregnant women in Malaysia.…”
Section: Relative Frequency Of Citation (Rfc) and Fidelity Level (Fl)mentioning
confidence: 92%
“…Le criblage phytochimique des extraits de feuilles, de racines, de tiges et de galles a montré la présence d'hydrates de carbone, de stéroïdes, de saponines, de flavonoïdes, d'alcaloïdes, de tanins, de saponines, de glycosides cardiaques, de coumarines, d'anthraquinones, d'acide ascorbique, d'hétérosides cardiotoniques, de cyanogènes et de terpénoides (Sule et al, 2001;Lamien et al, 2005;Williams et al, 2009;Sombié et al, 2011;Somboro et al, 2011;Mamman et Isa, 2013;Salihu et Usman, 2015;Al Shafei et al, 2016;Biu et al, 2016). Mariod et al (2016) ont déterminé, selon la procédure de Folin-Ciocalteu et calculée en équivalents d'acide gallique (EAG), les teneurs en composés phénoliques totaux dans les extraits de feuilles.…”
Section: Composition Chimiqueunclassified
“…Toujours au Nigeria, Mamman et Isa (2013) ont montré dans leur étude que Staphylococcus aureus, E. coli et Klebsiella étaient sensibles à l'extrait éthanolique des feuilles de G. senegalensis (Mamman et Isa, 2013). Djifaby et al (2012) du Burkina Faso ont observé dans leur étude que les extraits de feuilles possèdent une activité inhibitrice contre Bacillus cereus ATCC 13061 et Staphylococcus aureus ATCC 6538 qui présentaient une résistance à la pénicilline et à l'ampicilline.…”
Section: Activité Antimicrobienneunclassified
“…The areas of weaknesses were lack of tourism infrastructures and services, lack of tourist information and weak management of tourist area. Mamman and Isa (2013) conducted experiments to determine the preliminary phytochemical component and antibacterial activity of the leaves extract of Guierasenegalensis lam (Combretaceae) against three clinical isolates (Staphylococcus aureus, E. coli and Klebsiella species) using standard method of analysis. This study revealed that the leaves extract of Guierasenegalensis lam could be useful in the treatment of infections caused by Staphylococcus aureus, E. coli and Klebsiella species Bhandari (2013) analysed the trend of rainfall and temperature and their effect on the yield of major cereals Paddy/rice (Oryzasativa L.), wheat (Triticumaestivum L.), maize (Zea mays L.), millet (Eleusinecoracana Gaertn.)…”
Section: 'This Journal Provides Immediate Open Access To Its Contentsmentioning
confidence: 99%